2013
DOI: 10.1016/j.gie.2013.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic-derived novel cyst fluid biomarkers for pancreatic cysts: glucose and kynurenine

Abstract: Background Better pancreatic cyst fluid biomarkers are needed. Objective To determine whether metabolomic profiling of pancreatic cyst fluid would yield clinically useful cyst fluid biomarkers. Design Retrospective study. Setting Tertiary-care referral center. Patients Two independent cohorts of patients (n =26 and n = 19) with histologically defined pancreatic cysts. Intervention Exploratory analysis for differentially expressed metabolites between (1) nonmucinous and mucinous cysts and (2) malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 19 publications
10
57
1
1
Order By: Relevance
“…Glucose is commonly measured using spectrophotometric technologies that do not rely on antibody specifi city, and there is no heterogeneity in the glucose molecule as there might be with a tumor marker such as CEA. Th ere has only been one other study regarding the use of glucose to diff erentiate mucinous from non-mucinous cysts ( 9 ). In this study, metabolomic profi ling identifi ed glucose as a candidate molecule with an AUC of 0.88.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Glucose is commonly measured using spectrophotometric technologies that do not rely on antibody specifi city, and there is no heterogeneity in the glucose molecule as there might be with a tumor marker such as CEA. Th ere has only been one other study regarding the use of glucose to diff erentiate mucinous from non-mucinous cysts ( 9 ). In this study, metabolomic profi ling identifi ed glucose as a candidate molecule with an AUC of 0.88.…”
Section: Discussionmentioning
confidence: 80%
“…In an earlier study that included an exploratory metabolomic analysis of pancreatic cyst fl uid, glucose appeared to accurately diff erentiate non-mucinous from pre-malignant mucinous cysts with 94% sensitivity and 64% specifi city using a cutoff value of 66 mg/dl (AUC 0.88) ( 9 ). In the following study, we seek to further validate this observation regarding glucose using point-ofcare instruments in a larger cohort and compare its performance to CEA.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, studies have shown that cyst fluid amylase levels are similar in IPMNs and MCNs, and thus cannot be used to differentiate these two types of cysts [27]. There has been an interest in using cyst fluid glucose levels to differentiate IPMNs and MCNs from other types of cysts [28,29]. A recent study evaluated this in 153 patients all of whom had undergone surgical resection [30].…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Based on a preliminary experience, Park and co-workers have found that two metabolites, glucose and kynurenine, were differentially abundant in SCAs [52]. In particular, when cyst glucose levels of SCAs were compared with those of lesions that were not SCAs (pseudocysts, IPMNs, mucinous cystic neoplasms and cancer), the median cyst glucose level was significantly elevated, with an receiver operator characteristic curve of 0.93 (95% CI: 0.86-1.0).…”
Section: Cyst Fluid Analysesmentioning
confidence: 99%